Pengembangan Fasilitas Wisata Air Terjun Muara Jaya Kabupaten Majalengka Berdasarkan Persepsi Pengunjung - Dimas Pramono; Zulphiniar Priyandoko (Jurnal Planologi Unpas, 2015)
In the tourism sector, Majalengka get serious attention from the government because there is a plan construction of an international airport in the district development policies based on those Kertajati International Airport West Java, which is contained in the West Java Governor Decree No: 553.2 / 2271 / Dalprog. July 29, 2004, which is a designation for the construction of the International Airport in Majalengka, and toll roads Cisumdawu (Cileunyi-Sumedang-Dawuan) passing through the district of Majalengka. With the prospects of development in Majalengka it will automatically become a haven and a tourist destination for tourists both domestic and foreign. Waterfall Muara Jaya as one tourist attraction featured in Majalengka. But after observing directly to the tourist attraction Waterfall Muara Jaya and the response of the tourists who visit that the lack of facilities and yet orderly laying of the tourist facilities to support tourism activities in Waterfall Muara Jaya. It is necessary for the development of tourist facilities in Waterfall tourist attraction Muara Jaya. One way that is used for the analysis, namely by identifying traveler ratings against tourist facilities by using the formula Slovin sample size, in order to obtain the total sample of 100 respondents, then the directional menjelakan description of the analytical results. With the purposes of this study is to develop tourist facilities for tourist purposes is based on the perception of tourists and is based on the suitability of the tread weeks to travel is expected to increase tourism activities and the number of tourists visiting tourist attraction Waterfall Muara Jaya and can provide new economic activity for the community around.